The heavy precipitation event of December 2015 in Chennai, India - van Oldenborgh, G; Otto, F; Haustein, K; AchutaRao, K (American Meteorogological Society, 2017)
Extreme one-day rainfall caused widespread flooding in Chennai, India, in December 2015. No effect of global warming was detected, likely caused by aerosols counteracting greenhouse gases up to now.